Artificial intelligence and the politics of environmental governance: A critique of techno-solutionism in sustainability discourse - Moch Zihad Islami; Akhmad Khanif (Jurnal Sosiologi Dialektika, 2025)
Artificial intelligence (AI) has now been positioned as a crucial technology for sustainable environmental governance. However, the narratives constructed within it still tend to focus on technical benefits and rarely examine its political aspects critically. The purpose of this study is to reanalyze the socio-political sustainability narratives constructed within the discourse of AI technology. This study uses a qualitative, philosophical approach and draws on the literature for data collection. Literature data were collected from books, journal articles, and other relevant websites. The literature data were then analyzed interpretively and reflectively using a meta-philosophical approach. The results of this study show four main findings: (1) AI needs to be understood as a socio-technical system that is loaded with value and political aspects; (2) The discourse constructed on AI in environmental governance has three main dimensions: technical dimensions related to efficiency, political dimensions related to power aspects in technology, and philosophical dimensions related to how technology participates in shaping human views of the environment; (3) The use of AI has limitations, including in the form of environmental sustainability paradoxes, as well as epistemically being able to narrow the diverse knowledge space; (4) The planetary justice approach is offered as a more just alternative for both humans and the environment. The conclusion is that AI use in environmental governance must be bottom-up and involve democratic public participation to build an inclusive and just technology governance framework.